In‐Hospital Costs for Open versus Endoscopic Endonasal Approach for Craniopharyngioma Resection. (5th August 2022) - Parasher, Arjun K; Lerner, David K; Miranda, Stephen P.; Douglas, Jennifer E.; Glicksman, Jordan T; Alexander, Tyler; Lin, Theodore; Ebesutani, Darren; Kohanski, Michael; Lee, John YK; Storm, Phillip B; O'Malley, Bert W; et al.
Abstract : Objective: To determine the in‐hospital cost implications of an expanded endoscopic endonasal approach (EEEA) for craniopharyngioma resection relative to the traditional open transcranial approach. Methods: All craniopharyngioma surgeries performed at a single institution over a period from January 1st 2001 to October 31th 2017 were evaluated. The electronic medical record was reviewed for patient factors, tumor characteristics, and cost variables associated with each hospital stay and univariate regression analysis was performed using R software. Results: Thirty‐six patients met study criteria, including 22 undergoing an open approach and 14 undergoing an EEEA. There was a significantly longer average length of stay among patients undergoing open resection (21.5 vs. 10.6 days, p  = 0.024). The average total in‐hospital cost of a patient undergoing an EEEA was $58979.3 compared to $89142.3 for an open approach ( p  = 0.127). On univariate regression analysis, the total in‐hospital cost for a patient undergoing an open approach relative to an EEEA was $30163.0 ( p  = 0.127). The open approach was exclusively performed from study onset until April 2010 (16 patients). From April 2010 to August 2013, 6 open approaches and 5 EEEA were performed. The EEEA has been exclusively performed from August 2013 until the conclusion of our study period (9 patients). Conclusions: There has been a shift toward surgical resection of craniopharyngioma via an EEEA approach for amenable tumors. Our study demonstrates that the EEEA has become the preferred surgical approach at our institution, and shows that the EEEA is associated with shorter postoperative length of stay and lower total in‐hospital cost. Laryngoscope, 133:83–87, 2023 Abstract : Our work is a retrospective study over a 17‐year period examining the in‐hospital cost implications of an expanded endoscopic endonasal approach for craniopharyngioma resection relative to the traditional open transcranial approach. We found that, over the course of our study, there was a transition in dominant surgical approach from the open approach to the expanded endoscopic endonasal approach. The expanded endoscopic endonasal approach was associated with decreased average length of stay as well as decreased total in‐hospital costs relative to the traditional open approach.